Internal crisis communication crisis awareness, leadership and coworkership - Heide, Mats; Simonsson, Charlotte (Routledge, 2019)
"We live in a crisis society, with traditional media responding on a minute-by-minute basis on daily, seemingly inevitable, organizational crises. Whether crises have become more prevalent or we're simply more aware of them, they are now of great concern to organizations and crisis management and communication are a priority. Most organizations have a crisis response plan; many have dedicated crisis and security management staff. Yet much of the emphasis has been on action outside of the organization. Neglecting communication between managers and employees, they risk poor, inconsistent crisis management and the very real possibility of crisis escalation. Crisis management, like charity, begins in the home. Internal Crisis Communication is one of the first guides to communication inside organizations, before, during and after a crisis--not just on the acute crisis phase, to provide a complete and holistic guide for managers that will help them manage and contain crises. It includes an in-depth real-life case study, referred to throughout, form the author's own experience, which make practical application explicit and the methodology clear. Strengthened by rigorous academic research and tested in real-life crisis situations, the methods included in this book will be invaluable for communication professionals, security officers and crisis managers, as well as valuable reading for students and researchers interested in crisis and risk management"--Publisher.